ON THE EFFECT OF AMMONIUM AND LITHIUM IONS UPON FROG NERVE DEPRIVED OF SODIUM - Gallego, A. (The Rockefeller University Press, 1951)
An analysis has been made of the effect of ammonium and of lithium ions upon frog nerve deprived of sodium. Ammonium ions cannot substitute for sodium ions and restore the excitability of the nerve fibers; nor can they increase the L fraction of the membrane potential and the efficiency of the nerve reaction. Certain observations, however, indicate that the presence of ammonium ions outside the nerve fibers may delay the development of inexcitability in a sodium-free medium of nerve fibers restored by a moderate amount of sodium ions. Lithium ions can substitute for sodium and restore to nerve fibers of the A and C groups the ability to conduct impulses; the effect upon B fibers has not been investigated. Lithium cannot substitute for sodium in the role that sodium plays in the creation of the L fraction and in the establishment of the nerve reaction. In this respect lithium and sodium have opposite effects. This fact establishes an important difference between the two physiological responses that the nerve fibers can produce, the nerve impulse and the nerve reaction. With untreated nerve the depolarization of nerve by lithium ions at high concentrations is preceded by a phase of hyperpolarization; with nerve deprived of sodium the depolarization begins without delay.